Genetic variability, heritability, and genetic advance for quantitative traits of sorghum [Sorghum Bicolor (L.) Moench] genotypes at Fedis, Eastern Ethiopia - Mohammed Jafar; Bulti Tesso; Girma Mengistu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Sorghum is the second most important food crop after teff in Ethiopia. The objective of the study was to estimate the genetic variations, heritability, and expected genetic advances in the selected sorghum genotypes. Sixty-four sorghum genotypes were evaluated for 17 quantitative traits in 8x8 simple lattice designs at the Boko research site. The analysis of variance revealed highly significant differences among genotypes for all traits. The Phenotypic Coefficient Of Variation (PCV) ranged from 4.74% for days to flowering to 24.74% for panicle width, while Genotypic Coefficients Of Variation (GCV) ranged from 3.58% for leaf length to 20.33 % for panicle width. The highest PCV and GCV values were recorded for panicle width, head weight, and harvest index. Moderate PCV and GCV were recorded for grain filling period, grain filling rate, plant height, panicle length, and grain yield; indicating the effectiveness of selection based on the phenotypic performance of the genotypes. Broad sense heritability (H2) ranged from 24.74 % for biomass yield to 96.6% for head weight, whereas GAM ranged from 4.8% for biomass yield to 41.95% for panicle width. High H2 coupled with high GAM was observed for grain filling rate, panicle length, panicle width, head weight, grain yield, and harvest index; indicating that these characters are controlled by additive gene action and phenotypic selection for these characters will be effective. However, the information generated in the current study it can be useful for breeders who want to improve yield and yield contributing traits of sorghum.